Enteral Access Potentially Endangers Esophageal Carcinoma Patients Under Multi-modality Therapy: A Population-based Study - HUANG, CHUN-HOU; HSIEH, TSUNG-CHENG; CHANG, BEE-SONG; WANG, TSO-FU; WU, JUNG-LUN; CHANG, PI-CHUAN; PENG, TAI-CHU (Anticancer research, 2019)
This study aimed to evaluate the clinical outcome of esophageal cancer (EC) patients with enteral access (EA) undergoing multimodality therapy. This retrospective study analyzed data between 1997 and 2012 in Taiwan using the National Health Insurance Research Database. Patients with newly-diagnosed EC undergoing multimodality therapy were identified and classified as either EA group or no-EA group. The mortality incidence of EC patients with EA was significantly higher than in no-EA patients. The Cox model revealed the EA group had a higher risk of mortality than the no-EA group. Patients with chronic obstructive pulmonary disease (COPD) were at significantly higher risk of mortality compared to patients without COPD. EA in EC patients undergoing multimodality therapy was associated with an increased risk of mortality.